LEGAL IMPLICATIONS OF UNLAWFUL ACTS OF BUILDING ON FREEHOLD LAND AS DEBT COLLATERAL - Megawati, Charisma; Sugiharto, Dr. (IUS POSITUM: Journal of Law Theory and Law Enforcement, 2023)
Land and buildings are objects that play a crucial role and become basic needs in human life. Considering the great role of land rights, Law No. 5/1960 (Basic Agrarian Law) and its implementing regulations were enacted. Land ownership rights can be used as debt collateral encumbered by mortgage rights. In the process of transferring land ownership rights, legal actions are carried out. Legal actions that cause harm, contrary to laws and regulations, and the rights of others are categorized as unlawful acts (onrechtmatige daad). In the process of transferring land rights, an unlawful act may occur by constructing a building on the land of property rights. This normative juridical research examines positive legal materials using statutory, conceptual, analytical, and case study approaches. This research aims to determine the factors that cause unlawful acts by constructing buildings on property rights and the settlement of land disputes over property rights. The findings of this research revealed that the proof of title to the land of the Appellant (originally the Plaintiff) was valid and under the provisions of Law No. 5/1960 and Government Regulation No. 24/1997. However, the Appellant filed an exception regarding the lack of parties (plurium litis consortium) claim. The court of judges at the appellate level accepted the lawsuit without delving back into the proof of the subject matter. Thus, the judges only reached the exception of Appellant I and Appellant II.